1992
DOI: 10.2331/suisan.58.1517
|View full text |Cite
|
Sign up to set email alerts
|

Tension Change of Stressed and Unstressed Carp Muscles in Isometric Rigor Contraction and Resolution.

Abstract: The influence of ante-mortem stress on rigor mortis development was investigated in carp muscle. For this purpose, an isometric tension meter was constructed applying the interface assembly to the data acquisition. Immediately after death the stressed fish muscle generated strong contractile tension and entered the rigor state. Unstressed fish muscle maintained the relaxed state for an initial 21h. It then entered the rigor state and generated half the tension of the stressed fish. After both muscles generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
25
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 0 publications
9
25
0
Order By: Relevance
“…Lower muscle pH a few hours post mortem, and a more rapid decline during monitoring time in A group, are in agreement with what observed in sturgeon free to struggle before slaughtering (Izquierdo-Pulido et al, 1992) as well as in nonanesthetised carp (Nakayama et al, 1992). Fig.…”
Section: Rigor Index and Ph Evolution Fillet Shape Changes During Risupporting
confidence: 91%
“…Lower muscle pH a few hours post mortem, and a more rapid decline during monitoring time in A group, are in agreement with what observed in sturgeon free to struggle before slaughtering (Izquierdo-Pulido et al, 1992) as well as in nonanesthetised carp (Nakayama et al, 1992). Fig.…”
Section: Rigor Index and Ph Evolution Fillet Shape Changes During Risupporting
confidence: 91%
“…It is also suggested that the effect of rigor tension generation on the postmortem tenderization process is closely related to the physical nronerties and palatability of fish muscle.1) Ando et al 2) reported that the breaking strength of muscle of several fish species decreased sharply within 24 h after death, while maximal rigor was attained within this period. Nakayama et al 3) confirmed that tension was generated during rigor mortis development of carp muscle. The muscle contraction by rigor tension generation may induce the temporary increase of breaking strength, but the physical resistance of muscle structure to contraction may promote subsequent tenderization.…”
mentioning
confidence: 56%
“…High levels of stress at death have been reported to cause violent reactions in fish, including increasing muscular activity and influencing the post mortem changes in rigor mortis onset and resolution, drop of muscle pH immediately after death (Izquierdo-Pulido et al 1992;Nakayama et al 1992;Sigholt et al 1997), and decrease of ATP reserves (Sikorski et al 1990;Tornberg et al 2000). As with terrestrial animals, a close relation between the stress suffered before and during slaughter and the quality of the final product are found in fish (Azam et al 1989;Erikson 1997;.…”
Section: Introductionmentioning
confidence: 99%